Analysis of Malaysia’s future talents using time series - Farhan Arshad, Mohamad Rai’zuddin; Ramli, Nor Azuana; Ab Rashid, Nuryasmin (AMCS PRESS, 2022)
The unemployment rate has been increased after the pandemic and it also effects the youth unemployment rate. This research aims to investigate the issues relating to youth talents and employment. In achieving this aim, the main objective is set to forecast the future trend of Malaysia's labour force and employed rate in the upcoming 10 years by using time series analysis. Data of labour force are collected through Department of Statistics Malaysia Official Portal. After data cleaning and pre-processing, the data will be analysed by using Double Moving Average and Holt’s Method. The model will be evaluated using R-squared, root mean squared error and mean absolute percentage error. Based on the analysis, the Holt's Method is the best for the number of employed persons by age group (25 to 59 years old) as the model achieves better in each evaluation metric. To conclude, the demand for jobs also increases as the population increases. If this is not manageable, it can cause a higher rate of youth unemployment and the Twelfth Malaysia Plan to develop future talents might not be successful.